Dichloro-Phenyl-Benzotriazoles: A New Selective Class of Human Respiratory Syncytial Virus Entry Inhibitors - Piras, Sandra; Sanna, Giuseppina; Carta, Antonio; Corona, Paola; Ibba, Roberta; Loddo, Roberta; Madeddu, Silvia; Caria, Paola; Aulic, Suzana; Laurini, Erik; Fermeglia, Maurizio; Pricl, Sabrina (Frontiers in Chemistry, 2019)
Human Respiratory Syncytial Virus (RSV) is the primary cause of bronchopneumonia in infants and children worldwide. Clinical studies have shown that early treatments of RSV patients with ribavirin improve prognosis, even if the use of this drug is limited due to myelosuppression and toxicity effects. Furthermore, effective vaccines to prevent RSV infection are currently unavailable. Thus, the development of highly effective and specific antiviral drugs for pre-exposure prophylaxis and/or treatment of RSV infections is a compelling need. In the quest of new RSV inhibitors, in this work we evaluated the antiviral activity of a series of variously substituted 5,6-dichloro-1-phenyl-1(2)H-benzo[d][1,2,3]triazole derivatives in cell-based assays. Several 1- and 2-phenyl-benzotriazoles resulted fairly potent (µM concentrations) inhibitors of RSV infection in plaque reduction assays, accompanied by low cytotoxicity in human highly dividing T lymphoid-derived cells and primary cell lines. Contextually, no inhibitory effects were observed against other RNA or DNA viruses assayed, suggesting specific activity against RSV. Further results revealed that the lead compound 10d was active during the early phase of the RSV infection cycle. To understand whether 10d interfered with virus attachment to target cells or virus-cell fusion events, inhibitory activity tests against the RSV mutant strain B1 cp-52 – expressing only the F envelope glycoprotein – and a plasmid-based reporter assay that quantifies the bioactivity of viral entry were also performed. The overall biological results, in conjunction with in silico modeling studies, supported the conclusion that the RSV fusion process could be the target of this new series of compounds.